DIE EERSTE VRYDEIDSOORLOG: ENKELE ASPEKTE MBT DIE BRITSE SIENING VAN DIE BOERE EN DIE VERSKILLE TUSSEN BOER EN BRIT - Visser, G.E. (Scientia Militaria - South African Journal of Military Studies, 2012)
This article draws a comparison between the Boer and British Forces engaged in the war of 1880 - 1881 between the Zuid-Afrikaansche Republiek and England. It also depicts the gross underestimation of the Boer forces by the British during this war as main reason for the latter’s defeat.